Does size matter? – Reproductive success in Duttaphrynus melanostictus as a function of body size - Köhler, Gunther; Geiß, Katharina; Thammachoti, Panupong (Tropical Natural History, 2022)
We examined the mating pattern in the bufonid species Duttaphrynus melanostictus at a site in northeastern Thailand. During a breeding aggregation we determined snout–vent length (SVL) and body weight of amplectant males and females as well as of non-amplectant males. Additionally, we calculated the ratio of weight/SVL. In these parameters, there were no statistically significant differences between amplecting and non-amplecting males. We found a significant, moderate positive correlation for amplectant males and females SVL, indicating that larger females tend to mate with larger males. Thus, this positive correlation between the body sizes of mating partners is interpreted as evidence for size-assortative mating. We also provide a description of the advertisement call of this species from our study site.